Gender wage gaps in Australian workplaces: are policy responses working? - Chang, Joshua; Connell, Julia; Burgess, John; Travaglione, Tony (Emerald Group Publishing Limited, 2014)
Purpose – The purpose of this paper is to focus on the implications of the gender wage gap in Australia, before considering policy responses and their effectiveness at both the government and workplace levels. Design/methodology/approach – The method concerns an extensive literature review and an examination of secondary data and reports relating to workplace gender equality and data. Findings – While the gender wage gap in most OECD countries has decreased over time, in Australia the gap has increased, with the largest contributory factor identified as gender discrimination. Consequently it is proposed that current policy responses supporting women in the workplace appear to be ineffective in closing gender wage gaps. Research limitations/implications – Further research is recommended to identify the impact of gender equality policies on hiring decisions and whether such decisions include an unwillingness to hire or promote women. As findings were based on secondary data, it is recommended that future research include workplace surveys and case studies. Practical implications – It is suggested that articles such as this one can assist in guiding public policy and workplace decisions on gender wage equality issues, in addition to providing human resource leaders with the information to make better decisions relating to gender equality. Originality/value – This paper suggests that current policy responses may not only be ineffective in closing the gender wage gap, but may even exacerbate it as employers may avoid hiring women or continue to pay them less than men, due to costs incurred when attempting to meet policy directives.